Tax overpayments, tax evasion, and book-tax differences - Laszlo Goerke (Center for Economic Studies and ifo Institute (CESifo), 2008)
A strictly risk-averse manager makes joint decisions on a firm's tax payments and book profit declarations according to accounting standards. It is analysed how the incentives to overpay or evade taxes and to inflate book profits are influenced by (1) the composition of the manager's remuneration, (2) the ability to control the manager's actions, (3) the costs of making untruthful profit declarations, and (4) the tax rate. If the firm's owner or the government takes into account these effects when pursuing his own objectives, the changes in tax payments and book profit declarations become theoretically more ambiguous.
Keywords: H25; H26; M52; 330; executive compensation; financial accounting; tax evasion; Bilanzpolitik; Steuerkriminalität; Risikoaversion; Vergütungssystem; Führungskräfte; Theorie